2018
DOI: 10.2147/ndt.s163449
|View full text |Cite
|
Sign up to set email alerts
|

The interactive effects of ketamine and ethanol on dopamine expression in the ventral tegmental area of rats

Abstract: BackgroundA number of studies have demonstrated the significant and rapid antidepressant effects of ketamine, which is also known as a neurotoxic and illicit drug. Ketamine and alcohol are increasingly used together in clubs by teenagers and young adults. Previous studies have proven that chronic ketamine consumption induces a delayed and persistent activation of the dopamine (DA) system. However, the rewarding properties of recreational ketamine abuse remain unclear, and the underlying mechanisms of the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…The tyrosine hydroxylase was not observed to increase in the VTA by acute ethanol administration. 48 Furthermore, there was an increase in the dopamine outflow in the core but not the shell of the nucleus accumbens. 49 Besides, the difference in the detection time of tyrosine hydroxylase expression has been reported.…”
Section: Resultsmentioning
confidence: 97%
“…The tyrosine hydroxylase was not observed to increase in the VTA by acute ethanol administration. 48 Furthermore, there was an increase in the dopamine outflow in the core but not the shell of the nucleus accumbens. 49 Besides, the difference in the detection time of tyrosine hydroxylase expression has been reported.…”
Section: Resultsmentioning
confidence: 97%
“…In male rats, one study reported that co-administration of 20% alcohol with a high dose of ketamine (30 mg/kg, i.p.) increased VTA extracellular dopamine while ketamine on its own did not, suggesting that co-administering these drugs may amplify their rewarding properties (Zhang et al, 2018 ). Furthermore, tyrosine hydroxylase mRNA was increased with co-administration of alcohol and 30 mg/kg ketamine (Zhang et al, 2018 ).…”
Section: Interactions Between Alcohol and Ketaminementioning
confidence: 99%
“…increased VTA extracellular dopamine while ketamine on its own did not, suggesting that co-administering these drugs may amplify their rewarding properties (Zhang et al, 2018 ). Furthermore, tyrosine hydroxylase mRNA was increased with co-administration of alcohol and 30 mg/kg ketamine (Zhang et al, 2018 ). It has also been shown that co-administration of alcohol with a high concentration of ketamine (100 μM) amplified ketamine-induced apoptosis through heightened levels of intracellular Ca 2+ (Zuo et al, 2017 ).…”
Section: Interactions Between Alcohol and Ketaminementioning
confidence: 99%